2017
DOI: 10.1007/s11934-017-0680-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transurethral Resection of Bladder Tumors: Improving Quality Through New Techniques and Technologies

Abstract: Though a generally safe procedure, efficacy of TURBT in terms of complete tumor excision, appropriate pathologic diagnosis, and absence of complications can vary significantly with direct impact on patient outcomes. Application of new techniques including bipolar electrocautery and photodynamic enhancement continues to shape endoscopic management of bladder cancer and improve safety, tumor excision rates, and downstream outcomes. High-quality bladder tumor resection is essential for effective bladder cancer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…The authors concluded that the success of the procedure and results of recurrence rates are representative of the surgeon's skill and experience . The importance of a high‐quality TURBT has been stressed by many authors in recent years . Herr and Donat enumerated the most important aspects for performing a high‐quality TURBT, which include a wide and deep resection, ensuring detrusor muscle in the specimen, and obtaining negative microscopic margins.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the success of the procedure and results of recurrence rates are representative of the surgeon's skill and experience . The importance of a high‐quality TURBT has been stressed by many authors in recent years . Herr and Donat enumerated the most important aspects for performing a high‐quality TURBT, which include a wide and deep resection, ensuring detrusor muscle in the specimen, and obtaining negative microscopic margins.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies and developments have improved and changed the practice and increased the success of cystoscopy with transurethral resection of bladder tumors (TURBTs) [ 34 ]. The new techniques increase accuracy in the diagnosis of cancer and new technologies in cystoscopy endoscopic management increase the safety and patient outcomes of bladder cancer.…”
Section: Training For Transurethral Resection Of Bladder Tumorsmentioning
confidence: 99%
“…Bipolar, or plasmakinetic, TURBT has emerged in recent years as an alternative to standard monopolar TURBT. The main advantages of bipolar resection include the ability to use isotonic irrigation fluids to decrease the risk of TUR syndrome and potentially improved safety profile compared to monopolar energy [ 3 ]. Numerous studies that compared bipolar with monopolar TURBT have found decreased bladder injury associated with obturator nerve reflex [ 42–44 ] and improved detrusor sampling [ 45 ].…”
Section: New Resection Techniquesmentioning
confidence: 99%
“…Advances in modern WLC and TURBT include fiber-optic illumination, high definition cameras, and bipolar resection [ 3 ]. Nevertheless, significant shortcomings remain including missed tumors, incomplete resection, difficult differentiation of carcinoma in situ (CIS) from inflammation, and understaging [ 4 ].…”
Section: Introductionmentioning
confidence: 99%